'Covington' Sweetpotato Tolerance to Flumioxazin Applied POST-Directed. (March 2014) - Meyers, Stephen L.; Jennings, Katherine M.; Monks, David W.
Abstract : Field studies were conducted at Clinton, NC (2009, 2010), and Kinston, NC (2010), to determine 'Covington' sweetpotato tolerance to flumioxazin applied after transplanting. Flumioxazin was directed to 25% of the sweetpotato vine beginning at the distal end (shoot tip), 25% of the vine beginning at the proximal end (crown), or to the entire vine (over-the-top) and was applied at 2 or 5 wk after transplanting (WAP). Applications made at 2 WAP resulted in 10 to 16% foliar necrosis at 3 WAP. Necrosis was transient and ≤ 2% by 6 WAP. Stunting injury at 6 WAP for flumioxazin applied at 2 WAP was greatest (12%) with the over-the-top application, followed by crown (5%), and shoot tip (1%) applications. Applications made at 5 WAP resulted in 35, 23, and 15% foliar necrosis at 6 WAP for over-the-top, crown, and shoot tip applications, respectively. By 12 WAP, stunting injury for all treatments was ≤ 3%. No. 1, jumbo, canner, and total marketable sweetpotato yield of the nontreated check was 36, 670; 7, 610; 7, 170; and 51, 450 kg ha −1, respectively. No. 1 and total marketable sweetpotato yields were reduced when flumioxazin was applied at 2 or 5 WAP. No. 1 sweetpotato yield was reduced when flumioxazin was applied to the crown or over-the-top (27, 240 and 28, 330 kg ha −1, respectively). Sweetpotato receiving flumioxazin applied to the shoot tip had similar no. 1 (31, 770 kg ha −1 ) yields as the nontreated check, crown, and over-the-top applications. Total marketable sweetpotato yield was reduced by flumioxazin application to shoot tip, crown, and over-the-top (45, 350; 40, 100; 40, 370 kg ha −1, respectively). Neither flumioxazin application timing nor placement influenced either jumbo- or canner-grade sweetpotato yields. Currently, after-transplant applications of flumioxazin do not appear to be a suitable fit for POST weed control in North Carolina sweetpotato production systems.